How to factorise 6x^2-11x-10?

Firstly, when we need to factorise an expression like ax2 + bx + c, we should find two numbers m and n such that mn = ac and m+n = b. In this question, a = 6, b = -11, c = -10. So mn = -60 and m+n = -11. Let us use mn = -60 to find the values for m and n. Let write down the possible pairs: 1 and 60, 2 and 30, 3 and 20, 4 and 15, 5 and 12, 6 and 10. In each pair, one of them must be negative. To get m+n = -11, 4 and -15 is the only pair. So we have 6x2 -11x -10 = 6x2 +4x -15x -10 = 2x(3x + 2) - 5(3x + 2) = (2x - 5)(3x + 2).

Answered by Yunxi S. Maths tutor

15049 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the equation to the tangent to the curve x=cos(2y+pi) at (0, pi/4)


Find the surface area of a hand held fan (modeled with negligible depth) with radius 8 cm and a 60 degree angle at the centre


Find the derivative (dy/dx) of the curve equation x^2 -y^2 +y = 1.


Why do you differentiate in optimisation questions?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences